Identifying seaweed consumption by sheep using isotope analysis of their bones and teeth: Modern reference δ13C and δ15N values and their archaeological implications. (June 2020) - Blanz, Magdalena; Mainland, Ingrid; Richards, Michael; Balasse, Marie; Ascough, Philippa; Wolfhagen, Jesse; Taggart, Mark A.; Feldmann, Jörg
Abstract: Seaweed consumption by wild, feral and domesticated animals in coastal areas world-wide is currently likely widely underestimated. Seaweed consumption on the Orkney Islands by domesticated animals has become an established part of the archaeological literature, but the extent of seaweed consumption elsewhere is still largely unknown in archaeological contexts. The identification of small amounts of seaweed consumption by collagen δ 13 C and δ 15 N values remains problematic, as it is unclear to what extent seaweed consumption is reflected in skeletal tissues, and how results may vary between different tissues. In this study, modern sheep consuming known seaweed (predominantly kelp) and terrestrial diets on the Orkney Islands were analysed for δ 13 Ccollagen, δ 15 Ncollagen, δ 13 Cbone apatite and δ 13 Cenamel to provide a reference for archaeological studies. Seaweed and terrestrial vegetation were also analysed for δ 13 C and δ 15 N (n = 122). Seaweed δ 15 N values did not differ significantly from terrestrial vegetation on North Ronaldsay, indicating that δ 15 N is not a reliable indicator of seaweed consumption. In contrast, we confirmed that δ 13 C is a suitable marker for substantial seaweed consumption in all studied tissues in herbivorous diets in the absence of C4 plants. The consumption of both seaweed and terrestrial vegetation led to a large degree of variability in δ 13 C results (−19.1 to −11.5‰) within one herd kept under a consistent management system, due to differences in the amount of seaweed consumed by the individual sheep. However, when only small amounts of seaweed are consumed (<25%), this may not be evident in the δ 13 Ccollagen data. In contrast, when seaweed-consumption occurs primarily in winter, spring-born lambs may be expected to have substantially higher δ 13 C values than their mothers. This study emphasises the need for modern reference data in archaeology, and may aid the identification of seaweed consumption by herbivores globally. Highlights: Substantial seaweed consumption led to elevated collagen and bone apatite δ 13 C. Collagen δ 15 N is not a reliable indicator of seaweed consumption. Seaweed as an additional foodstuff can cause a wide range of δ 13 C values in a herd. Seasonal seaweed consumption by ewes can lead to higher δ 13 C values in their lambs.